2015
DOI: 10.1074/mcp.m114.041632
|View full text |Cite
|
Sign up to set email alerts
|

N-glycomic Profiling as a Tool to Separate Rectal Adenomas from Carcinomas*

Abstract: All human cells are covered by glycans, the carbohydrate units of glycoproteins, glycolipids, and proteoglycans. Most glycans are localized to cell surfaces and participate in events essential for cell viability and function. Glycosylation evolves during carcinogenesis, and therefore carcinoma-related glycan structures are potential cancer biomarkers. Colorectal cancer is one of the world's three most common cancers, and its incidence is rising. Novel biomarkers are essential to identify patients for targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 27 publications
4
54
0
Order By: Relevance
“…Recent glycomics and glycoproteomics‐centric studies have demonstrated that PMPs are also elevated glycosylation signatures associated with various human cancers including those of ovarian (Everest‐Dass et al ., ; Chen et al ., ), colorectal (Joosten et al ., ; Balog et al ., ; Sethi et al ., ; Kaprio et al ., ; Holst et al ., ), breast (Lee et al ., ; Chen et al ., ), lung (Hua et al ., ; Ruhaak et al ., ; Wang et al ., ), paraganglioma (Leijon et al ., ), glioblastoma multiforme (Becker et al ., ), skin (Moginger et al ., ) and prostate (Shah et al ., ) origin. By systematically interrogating a very large collection of nearly 500 N ‐glycomics LC‐MS/MS data sets obtained from 11 cancer types and subtypes, we have obtained solid evidence that PMGs are significant features of human cancers and, at least in part, expressed on cancer cell surfaces (S. Chatterjee, L. Y. Lee, R. Kawahara, J. L. Abrahams, B. Adamczyk, M. Anugraham, C. Ashwood, Z. Sumer‐Bayraktar, M. T. Briggs, J. H. L. Chik, A. Everest‐Dass, S. Förster, H. Hinneburg, K. R. M. Leite, I. Loke, U. Möginger, E. S. X. Moh, M. Nakano, S. Recuero, M. K. Sethi, M. Srougi, K. Stavenhagen, V. Venkatakrishnan, K. Wongtrakul‐Kish, S. Diestel, P. Hoffmann, N. G. Karlsson, D. Kolarich, M. P. Molloy, M. H. Muders, M. K. Oehler, N. H. Packer, G. Palmisano & M. Thaysen‐Andersen, in preparation).…”
Section: Human Pmps: Cues From Higher and Lower Eukaryotesmentioning
confidence: 99%
“…Recent glycomics and glycoproteomics‐centric studies have demonstrated that PMPs are also elevated glycosylation signatures associated with various human cancers including those of ovarian (Everest‐Dass et al ., ; Chen et al ., ), colorectal (Joosten et al ., ; Balog et al ., ; Sethi et al ., ; Kaprio et al ., ; Holst et al ., ), breast (Lee et al ., ; Chen et al ., ), lung (Hua et al ., ; Ruhaak et al ., ; Wang et al ., ), paraganglioma (Leijon et al ., ), glioblastoma multiforme (Becker et al ., ), skin (Moginger et al ., ) and prostate (Shah et al ., ) origin. By systematically interrogating a very large collection of nearly 500 N ‐glycomics LC‐MS/MS data sets obtained from 11 cancer types and subtypes, we have obtained solid evidence that PMGs are significant features of human cancers and, at least in part, expressed on cancer cell surfaces (S. Chatterjee, L. Y. Lee, R. Kawahara, J. L. Abrahams, B. Adamczyk, M. Anugraham, C. Ashwood, Z. Sumer‐Bayraktar, M. T. Briggs, J. H. L. Chik, A. Everest‐Dass, S. Förster, H. Hinneburg, K. R. M. Leite, I. Loke, U. Möginger, E. S. X. Moh, M. Nakano, S. Recuero, M. K. Sethi, M. Srougi, K. Stavenhagen, V. Venkatakrishnan, K. Wongtrakul‐Kish, S. Diestel, P. Hoffmann, N. G. Karlsson, D. Kolarich, M. P. Molloy, M. H. Muders, M. K. Oehler, N. H. Packer, G. Palmisano & M. Thaysen‐Andersen, in preparation).…”
Section: Human Pmps: Cues From Higher and Lower Eukaryotesmentioning
confidence: 99%
“…Taking into account the prevalence of pancreatic cancer, the expected number of CA19.9 determinations was calculated to be 10-fold lower than the number of tests actually performed in a western country [111]. This is probably due to the assumption that serum CA19.9 values may help the differential diagnosis of several gastrointestinal diseases, including cancers arising not only in the pancreas [114,115,116], but in the colon [117], stomach [118,119], and bile ducts [120]. In this regard, it is important to recall that the synthesis, expression, and secretion of CA19.9 was demonstrated in many healthy tissues, including the pancreas [121] and the bile ducts [122].…”
Section: Role In Diagnosismentioning
confidence: 99%
“…Consequently, exogenous origin(s) of paucimannosylation could not be ruled out. Mammalian paucimannosylation was supported by immunohistochemistry and immunocytochemistry of selected human and murine tissues and cells using paucimannose-reactive antibodies (12)(13)(14). In general, however, mammals including human and mice have usually been reported to lack protein paucimannosylation (15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%